Argonne Mine, preparing a blast - Anderson, F. G.; Arthur Lakes Library; Russell L. and Lyn Wood Mining History Archive; United States. Bureau of Mines (Colorado School of Mines. Arthur Lakes Library, 1947)
Date scanned: 2002-6-12. H-5; Preparing a blast. Bucyrus-Erie 27-T churn drill with bell guide chained to mast, sheet steel hood for protection of driller, winter enclosure, and standard guards over moving parts. Note: Churn drill operated by gasoline engine and proximity of pile of explosives to this engine. Argonne Mine, The M. A. Hanna Company, Keewatin, Minnesota. - F. G. Anderson - July 24, 1947. Held in the Russell L. and Lyn Wood Mining History Archive, Arthur Lakes Library, Colorado School of Mines. Donor: United States Bureau of Mines. Miners prepare a blast using a churn drill at the Argonne Mine. Notes accompanying this image infer a safety issue from the explosives located near a gasoline engine. The Argonne open pit iron mine in the Mesabi Range in Itasca County, Minnesota was operated by the M. A. Hanna Company. The M. A. Hanna Company was one of the large mining companies that moved into the iron areas of the Lake Superior region in the early 1900s, consolidating smaller properties and engaging in exploration for other economic deposits. The Company was dissolved in 1965, then resurrected in 1985.